247 Unusual presentation to an emergency department. Issue 6 (27th May 2022) - Yoganathan, Katie; Shah, Apeksha; Marta, Monica
Abstract : 24-year-old man presented with drowsiness, worsening cognitive impairment and a mixed movement disorder. He was adopted as a child and was reported to be independent and working one year before admission, but progressively slow and unable to self-care since. On examination, he was cognitively impaired on all domains. He had increased tone, brisk reflexes and extensor plantars. There were dysto- nia-parkinsonian features of dystonic tremor and bradykinesia, slow saccades and oculomotor apraxia, along with motor impersistence. After exclusion of chronic infections, the working diagnosis was of a neurodegenerative movement disorder. Whilst there was no overt chorea, the differentials for juvenile Huntingdon's disease (HD) were explored, and HD ultimately confirmed on genetic testing. Learning Points: Juvenile HD patients may not have chorea but may be rigid or parkinsonian. Slow saccades are most prominent in juvenile HD patients, even early. Involuntary movements are often partially suppressible, and mild chorea is easily overlooked. Look for involuntary head turns, fidgety movements of the fingers and toes, frequent blinking and odd facial expressions. Test for motor impersistence in these individuals. Gait may appear normal but tandem walk may bring out chorea, imbalance, or other problems. katieyoganathan@gmail.com